Biomechanical competence of six different bone screws for reconstructive surgery in three different transplants: Fibular, iliac crest, scapular and artificial bone. Issue 6 (June 2016) - Pietsch, Arnold P.; Raith, Stefan; Ode, Jan-Eric; Teichmann, Jan; Lethaus, Bernd; Möhlhenrich, Stephan C.; Hölzle, Frank; Duda, Georg N.; Steiner, Timm
Abstract: The goal of this study was to determine a combination of screw and transplantation type that offers optimal primary stability for reconstructive surgery. Fibular, iliac crest, and scapular transplants were tested along with artificial bone substrate. Six different kinds of bone screws (Medartis © ) were compared, each type utilized with one of six specimens from human transplants (n = 6). Controlled screw-in-tests were performed and the required torque was protocolled. Subsequently, pull-out-tests were executed to determine the retention forces. The artificial bone substitute material showed significantly higher retention forces than real bone samples. The self-drilling screws achieved the significantly highest retention values in the synthetic bone substitute material. Cancellous screws achieved the highest retention in the fibular transplants, while self-drilling and cancellous screws demonstrated better retention than cortical screws in the iliac crest. In the scapular graft, no significant differences were found between the screw types. In comparison to the human transplant types, the cortical screws showed the significantly highest values in the fibula and the lowest values in the iliac crest. The best retention was found in the combination of cancellous screws with fibular graft (514.8 N + −252.3 N). For the flat bones (i.e., scapular and illiac crest) we recommend the cancellous screws.